Security study on C1G2 UHF RFID air interface - Wang, Bin (2012)
This project studies EPC C1G2 UHF RFID air interface protocol which defines the communication between C1G2 RFID readers and tags. The EPC C1G2 air interface protocol standard defines the physical and logical requirement for the passive-backscatter, interrogator-talks-first (ITF) Radio Frequency Identification (RFID) system operating in 860-960 MHz frequency range which is specified by EPCGlobal.